Pengaruh Metode Lattice Terhadap Hasil Belajar Operasi Perkalian Bilangan Cacah dengan Menggunakan Model PBL di Kelas IV Sekolah Dasar - Ahmad, Syafri; Siregar, Julinda Khoirunnisa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the effect of using the lattice method on the learning outcomes of multiplication operations of integers in class IV elementary school. This research is experimental research in the form of Quasi Exsperimental Type Nonequivalent Control Group Design. The sampling technique used cluster random sampling. In hypothesis testing, simple linear regression test, correlation analysis, and t test were used. Based on correlation analysis, the experimental class obtained rxy 0.825 which is categorized as very strong. The coefficient determination value obtained is 68.06%, so it can be interpreted that the use of the lattice method has an effect of 68.06% on the learning outcomes of multiplying small numbers in class IV. Through the t-test in the form of an independent t-test based on the posttest scores of the experimental and control classes, a tcount of 2.04613 was obtained with a ttable of 2.014 at a significance level of 0.05. When the tcount and ttable are compared, 2.04613> 2.014. This means that Ho is rejected, and Ha is accepted, so it can be concluded that there is a significant effect of using the lattice method with the PBL model on the learning outcomes of multiplication operations of small numbers in class IV elementary schools